“Solvent/non-solvent” treatment as a method for non-covalent immobilization of gelatin on the surface of poly(l-lactic acid) electrospun scaffolds; Colloids and Surfaces B: Biointerfaces; Vol. 177 - Goreninsky S. I. Semen Igorevich; Gulyaev R. O. Roman Olegovich; Stankevich K. S. Ksenia Sergeevnahttps://online.sberbank.ru/CSAFront/index.do; Danilenko N. V. Nadezhda Viktorovna; Bolbasov E. N. Evgeny Nikolaevich; Golovkin A. S. Aleksey Sergeevich; Mishanin A. I. Aleksandr; Filimonov V. D. Viktor Dmitrievich; Tverdokhlebov S. I. Sergei Ivanovich (2019, 2019)
Title screen